Evaluation of Physics-informed Neural Network Solution Accuracy and Efficiency for Modelling Aortic Transvalvular Blood Flow. - Du Toit, Jacques Francois (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.